Haematological Modulation Associated with Sub-Chronic Oral Administration of Extracts of Simarouba glauca (Paradise tree) in Male Wister Rats: A Comparative Study - Ishaq Sammydavies E. Osagie-Eweka; Khadijah A. Isimekhai (Biology, Medicine, & Natural Product Chemistry, 2026)
Simarouba glauca has been reported to possess various bioactive compounds with therapeutic potentials; with paucity of data on safety; hence, the study aimed to evaluate the effects of aqueous, ethanol and methanol leaf extracts of Simarouba glauca on hematological indices of male Wistar rats. The study was conducted according to the guidelines of organization for economic co-operation and development (OECD), No. 425; with a total of thirty male Wistar rats; divided into ten groups of n >= 3. Experimental rats were administered Simarouba glauca Leaf extracts at 500, 1000 and 2000 mgkg-1 body weight, respectively; while the control group received feed and water only ad libitum daily for 30 days. Selected hematological indices were evaluated. Groups administered respective doses of ethanol and methanol leaf extracts demonstrated significant (p < 0.05) dose-dependent elevation of red blood cell; significant (p< 0.05) rise in the white blood cell count of groups administered aqueous, ethanol and methanol extracts respectively at high doses; whereas, at 500 mgkg-1 of respective extracts, there were no differences (p > 0.05) in white blood cell count. Monocytes increased (p < 0.05) in groups administered respective doses of the extracts; while lymphocytes increased in groups administered respective doses of ethanol extract. Although, the extracts elicited alterations in white blood cells at higher doses; extract(s) did not induce anemia. Interestingly, extracts stimulated marked increases in red blood cell counts; an indication of the seemingly erythropoietic potentials of the extracts.